Experimental study on settling velocity of soil particles in dredged slurry. Issue 6 (18th August 2017) - Zhang, Nan; Zhu, Wei; He, Hongtao; Lv, Yiyan; Wang, Shengwei
ABSTRACT: Studying sedimentation and consolidation of dredged slurry has significant implications to the design of storage yard and subsequent ground improvement. In this study, settling velocity of soil particles in dredged slurry during sedimentation and consolidation processes was investigated using an improved multilayer extraction sampling (MES) method. A series of sedimentation column tests were performed on dredged slurry with three different initial water contents. Distributions of volume of soil particles and density of dredged slurry were first obtained by the MES method, settling velocity of soil particles was then calculated by volume flux function approach. It was found that the density and velocity inflection points can be used to distinguish the settling zone and the consolidation zone. The experimental results reveal that the velocity of soil particles was quite low and monotonically decreased with sedimentation height at low initial water content throughout the whole test period, whereas it was increased at 0–1 hours and almost remained constant at 1–7 hours in the settling zone at high initial water content. The effects of initial water content on sedimentation and consolidation mode of dredged slurry and the settling velocity of soil particles were discussed. The relationship between settling velocity of soil particles and particle diameter was also studied. It is indicated that the measured velocity of soil particles was much lower than that calculated by the Stokes equation, and it was related to 0.4881–0.5906 order of particle diameter at 0–1 hours and 0.1117–0.1825 order of particle diameter at 1–7 hours for the test slurries.